Estudio de pre factibilidad para la fabricación e instalación de estructuras metálicas a partir de diseños personalizados. (2020)
The present study is entitled "Pre-feasibility study for the manufacture and installation of metal structures from custom designs"; It is carried out with the purpose of investigating what are the characteristics of the potential market, the technical, financial, environmental and legal characteristics that make it possible to determine if the activity of manufacturing and installation of metal structures under customized designs is feasible. For the development of the work and to answer this question, the authors carry out a documented theoretical review on the problems of the development of the metalworking industry and on the designs of metal structures in the Colombian context, as well as aspects that can help determine the feasibility of the project. A methodological design directed to the realization of a quantitative study is applied where the surveys that are carried out online are used as an instrument, sending a Google form via email to potential clients. Subsequently, adding to this market study the development of analyzes on technical, financial and environmental aspects, the viability of this activity is established, where, with respect to the market study, the main companies that could compete with the business idea and The main difficulty is the lack of knowledge of potential customers about the benefits of custom designs in metal roofs. Regarding the technical study, the competitive advantages of metal roofs and the Puente Aranda sector for this type of business are shown, indicating a possible distribution of the physical plant. In the environmental aspect, it is recommended to follow the guidelines of the ISO 14000 family of standards, for the management of formats, within a possible quality system and in the financial evaluation, an Internal Remuneration Rate (IRR) of 30.04% is reached. Keywords: Pre feasibility, structure, metal, design, novel, elegant.